Thermal analysis of a fully wet porous radial fin with natural convection and radiation using the spectral collocation method - Khani, F.; Darvishi, M.T.; Gorla, Rama Subba Reddy; Gireesha, B. J. (Zielona Góra: Uniwersytet Zielonogórski)
Heat transfer with natural convection and radiation effect on a fully wet porous radial fin is considered. The radial velocity of the buoyancy driven flow at any radial location is obtained by applying Darcy`s law. The obtained non-dimensionalized ordinary differential equation involving three highly nonlinear terms is solved numerically with the spectral collocation method. In this approach, the dimensionless temperature is approximated by Chebyshev polynomials and discretized by Chebyshev-Gausse-Lobatto collocation points.
Keywords: wet porous radial fin; natural convection; radiation; thermal analysis; spectral collocation method